2015
DOI: 10.1093/ehjcvp/pvv040
|View full text |Cite
|
Sign up to set email alerts
|

Cenderitide: structural requirements for the creation of a novel dual particulate guanylyl cyclase receptor agonist with renal-enhancingin vivoandex vivoactions

Abstract: Aim Cenderitide is a novel dual natriuretic peptide (NP) receptor chimeric peptide activator, which targets the particulate guanylyl cyclase B (pGC-B) receptor and pGC-A unlike native NPs. Cenderitide was engineered to retain the anti-fibrotic properties of CNP/pGC-B with renal enhancing actions facilitated by fusion to the carboxyl-terminus of Dendroaspis NP (DNP), a pGC-A agonist, to CNP. Here, we address significance of the DNP carboxyl-terminus in dual pGC receptor activation and actions of cenderitide com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 35 publications
(52 reference statements)
4
24
0
Order By: Relevance
“…4), which needs confirmation in a larger trial. These renal actions especially related to GFR are consistent with pGC-A action, as supported by previous studies in isolated glomeruli [38].…”
Section: Cenderitide (Cd-np) For Heart Failure: Clinical Studiessupporting
confidence: 90%
See 1 more Smart Citation
“…4), which needs confirmation in a larger trial. These renal actions especially related to GFR are consistent with pGC-A action, as supported by previous studies in isolated glomeruli [38].…”
Section: Cenderitide (Cd-np) For Heart Failure: Clinical Studiessupporting
confidence: 90%
“…The importance of the unique structure of Cenderitide was recently reported by, Lee et al [38] Specifically, Lee and co-workers addressed the hypothesis that the 15-AA carboxyl-terminus of DNP, which is fused to CNP, uniquely facilitates dual pGC-A and pGC-B activation produced by Cenderitide. The actions of Cenderitide on cGMP activation in vitro in HEK293 cells selectively overexpressing human pGC-A or pGC-B were compared to native CNP and three variants of Cenderitide with altered carboxyl-termini.…”
Section: Cenderitide (Cd-np) For Heart Failure: Preclinical Drug Discmentioning
confidence: 96%
“…In vivo studies revealed that CD-NP, like ANP, BNP, and DNP (but unlike CNP) possesses renal-enhancing actions through pGC-A/cGMP activation. CD-NP was under clinical trials to treat cardiorenal syndrome [ 41 ]. However, Capricor Beverly Hills, California, recently completed an additional study with patients having stable heart failure in combination with moderate renal impairment.…”
Section: Snake Venom Peptides and Their Potential Pharmacological mentioning
confidence: 99%
“…Compared with ANP, BNP, and CNP, DNP has elongated N-and C-termini and is more stable against neutral endopeptidase 38 , which is the primary inactivator of natriuretic peptides. Based on the enhanced stability and high potency of DNP, chimeras of DNP and other natriuretic peptides have been created and assessed in clinical trials for heart failure 39,40 . Thus, understanding the difference between the binding of ANP and DNP to ANPR is essential to future drug discovery and research for heart failure therapies.…”
Section: Discussionmentioning
confidence: 99%